HOW to make a mix of low glycemic index flours for a good Neapolitan pizza for patients with diabetes. Issue 4 (July 2020) - Della Corte, T.; Gentile, S.; Guarino, G.; Satta, E.; Romano, C.; Alfarone, C.; Strollo, F.
Abstract: Background and aims: Our recent data document that a low glycemic index (LGI) Neapolitan pizza prepared with a mix of Kamut and whole wheat flours plus Glucomannan, (i) has a lower impact on postprandial hyperglycemic spikes than pizza made of whole wheat flour, (ii) is pleasant and appreciated as traditional one and (iii) does not cause any gastro-intestinal troubles. The aim of our study was to describe the validation process underlying the identification of the right mix of those elements for a LGI pizza preventing gastro-intestinal disturbances. Methods: we described all procedures followed to make good products with different combinations of the three components and a series of tests made by four well-experienced professional pasta-making masters, one nutritionist, five diabetologists, one nurse and twenty volunteers with T1DM. Results: we could identify the best workable and most suitable flour mix to achieve both pleasant taste and low glycemic impact proving to be efficient in real-life twin paper providing results from diabetic patients. Conclusions: this kind of food will certainly help people with diabetes eat pizza without risking any serious deterioration of their own glucose control while fully enjoying socially active life. Highlights: Widespread pizza consumption causes sustained hyperglycemia in people with diabetes (DM). Low glycaemic index (LGI) flour pizzas proposed so far to overcome this problem taste bad. The LGI pizza we developed could encourage DM patients to enjoy both socialization and taste. We provide details on how to successfully prepare it from a mix of flours and glucomannan.